USING HIGHER ORDER QUESTIONS TO STIMULATES STUDENTS’ SPEAKING ACTIVITIES IN STUDENT CENTERED CLASSROOM - Ai Erna Dewi (Journal of English Education Program (JEEP), 2020)
Teacher feedback stipulation is a necessity for students especially in the process of writing. The present study, therefore, aims at 1) Figuring out how the teacher uses higher order questions to stimulate students speaking activities in student centered classroom; and 2) To investigate what classroom activities will be indicative in student centered speaking class by means of higher order questions. The present study implemented case study with the type of observation for the qualitative design. The present study involved 19 students as participants. Classroom observation, questionnaire and teacher interview were carry out to obtain the data in the present study. Afterwards, classroom activities observation and documentation of students’ test were conducted to get the data. Based on the observations result, higher order questions is one of the most frequently used strategies in classroom teaching, as well as the most influential teaching skill. It is a useful way for teachers to get and convey information, and to obtain feedback from students. Teachers can also use it to communicate with their students.  Effective questioning in class can encourage students to give relative and complete answers. It can activate students’ thought, develop their opinion, express their ideas and discussion class as well, make students active in classroom (student centered) and the teacher as facilitators. Based on these findings, it is recommended that English teachers should be provided with more training on employing of higher order questions to facilitate students’ thinking for themselves and develop the students’ mind by encouraging their English speaking.  Keywords: higher order questions, student centered, speaking activities